Bifocal 532/1064 nm alternately illuminated photoacoustic microscopy for capturing deep vascular morphology in human skin. (2nd October 2021) - Wang, Z.; Yang, F.; Ma, H.; Cheng, Z.; Zhang, W.; Xiong, K.; Shen, T.; Yang, S.
Abstract: Background: As a promising technology, photoacoustic microscopy (PAM) plays a critical role in diagnosis and assessment of dermatological conditions by providing subtle vascular networks non‐invasively. However, the established PAMs are insufficient for clinical dermatology when faced with complex structures of human skin instead of animal models owing to high melanin content and superimposed vasculature for Asians, which cannot balance the spatial resolution and the imaging depth. Objectives: To evaluate the ability of bifocal 532/1064‐nm alternately illuminated photoacoustic microscopy (BF‐PAM) to non‐invasively reveal the morphological structure of human skin for improving the diagnosis and therapeutic efficacy of skin diseases. Methods: A BF‐PAM was developed to capture biopsy‐like information of human skin from epidermis to hypodermis. The optical foci of the two excitation beams are staggered in the axial direction to form an extended depth‐of‐field, which can maintain the lateral resolution and the contrast of PA image. Results: The imaging capability of the BF‐PAM was demonstrated by depicting the vascular morphology of multilayered skin with imaging depth of ˜3 mm. Furtherly, vascular malformations in port‐wine stains skin were quantitatively assessed without the need for any contrast agent, and the distribution, depth and diameter of the ectatic vessels can determine an optimal treatment protocol for port‐wine stains lesions. Conclusions: The quantitative vascular morphology in the dermis can be used to accurately assess vascular characteristics, in which case it enables clinicians to determine optimum treatment parameters in individual patients. As a non‐invasive imaging technique, BF‐PAM holds great potential to provide objective assessment to enhance the therapeutic efficacy. Ethical statement: The study was conducted in accordance with the Declaration of Helsinki (as revised in 2013). The study was approved by the Chinese Ethics Committee of Registering Clinical Trials (ChiECRCT20200184) and registered with Chinese Clinical Trial Registry (ChiCTR2000034400). Before skin imaging, written informed consent was taken from all individual participants.